(untitled) (Fiep Bulletin - online, 2012)
The history of the FIEP CHILE Committee dates back to the end of 1889, when Mr. JOAQUINCABEZAS GARCIA, a young Chilean Elementary School teacher, went to Sweden for his first studies on ManualWorks and Gymnastics with the famous professor Luys. Later, he went back to Sweden several times and, in oneof them, in 1918, he got to know and committed himself to the International Federation of Gymnastics Ling. Thisway, in 1923, during the creation of the Gran Movimiento, authorities of the International Federationcommunicated his incorporation as an active member. Another opportunity for Cabezas, was his visit to the 1stLINGIADA, in 1939. History goes on with Mr. Luis Bisquertt Susarte, who attends the 2nd LINGIADA in 1949, where he getstotally committed to the whole FIEP Movement, thus transcribing in the Chilean Magazines of Physical Education,during almost three years, one by one, all of the events (conferences, meetings, presentations, visits) whichcharacterized this second event in homage to Gran Per Henrik LING. After coming back, besides publicizing theLINGIADA, Dr. Bisquertt constitutes the First FIEP-CHILE COMMITTEE, 1950.